Adaptation Strategy for Music Learning at SMA Negeri 5 Purwokerto during the COVID-19 Pandemic - Wisnugraha, Azhardi; Utomo, Udi; Malarsih, Malarsih (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the problems, adaptation strategies, and factors that influenced music learning at SMA Negeri 5 Purwokerto during the COVID-19 pandemic. This study used a descriptive qualitative approach. The research was conducted at SMA Negeri 5 Purwokerto. Data collection techniques used observation, interviews, and documentation studies. Validation of data used triangulation techniques with data analysis techniques using interactive models. This study found that in the online learning process at SMA Negeri 5 Purwokerto, the problems faced were differences in student understanding and limited facilities and infrastructure. There are three strategies for adapting music learning at SMA Negeri 5 Purwokerto during the Covid-19 pandemic. First, the method adaptation strategy is carried out using the blended learning method. Second, the media adaptation strategy is carried out by changing the lesson plans, using smartphones, laptops, and video conferencing through the Google Classroom application, Zoom, and Whatsapp. Third, the assessment adaptation strategy is carried out by assessing student attendance, assessing assignment portfolios and exams. Factors that influence online learning of music subjects at SMA Negeri 5 Purwokerto consist of internal and external factors. Students' internal factors can be seen from intelligence, talent, student health conditions, learning methods, understanding and interests, and motivation. The most influencing factors are intelligence & talent, student understanding and interest, and motivation. Meanwhile, the external factors in this study are the physical environment, school, and family environment. The external factor that influences the student learning online the most is the physical environment factor. The purpose of this study was to analyze the problems, adaptation strategies, and factors that influenced music learning at SMA Negeri 5 Purwokerto during the COVID-19 pandemic. This study used a descriptive qualitative approach. The research was conducted at SMA Negeri 5 Purwokerto. Data collection techniques used observation, interviews, and documentation studies. Validation of data used triangulation techniques with data analysis techniques using interactive models. This study found that in the online learning process at SMA Negeri 5 Purwokerto, the problems faced were differences in student understanding and limited facilities and infrastructure. There are three strategies for adapting music learning at SMA Negeri 5 Purwokerto during the Covid-19 pandemic. First, the method adaptation strategy is carried out using the blended learning method. Second, the media adaptation strategy is carried out by changing the lesson plans, using smartphones, laptops, and video conferencing through the Google Classroom application, Zoom, and Whatsapp. Third, the assessment adaptation strategy is carried out by assessing student attendance, assessing assignment portfolios and exams. Factors that influence online learning of music subjects at SMA Negeri 5 Purwokerto consist of internal and external factors. Students' internal factors can be seen from intelligence, talent, student health conditions, learning methods, understanding and interests, and motivation. The most influencing factors are intelligence & talent, student understanding and interest, and motivation. Meanwhile, the external factors in this study are the physical environment, school, and family environment. The external factor that influences the student learning online the most is the physical environment factor.